A Novel Method of Measuring Transformer Oil Interfacial Tension Using UV-Vis Spectroscopy - Abu Bakar, Norazhar; Abu-Siada, Ahmed (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2016)
In this article we propose an alternative method of measuring the IFT of transformer oil, using ultraviolet-to-visible (UV-Vis) the IFT of an oil sample and its spectral response parameters (bandwidth and peak absorbance).